Digital Literacy via Readersâ€™ Responses towards Humor Presented in â€œ9GAG Memesâ€ - Listiyaningsih, Fina; Rukmini, Dwi; Sutopo, Djoko (English Education Journal, 2020)
Language education by using digital literacy via reader response approaches towards humor presented in social media will attract the student attention during learning process. The purpose of this research is to analyze the text produced by learners in order to explain how they provide responses towards humorous, fearing, annoying, pitiful, and confusing memes.This research is a qualitative research. The approach of the research is descriptive approach. This research was a readers response analysis focusing on descriptive qualitative. The data collecting done by observation, documentation and questionnaires. The subject of the study are students of SMA Negeri 1 Pecangaan Jepara. The method applied in this research is General Theory of Verbal Humor and Reader â€˜s Response Theory as the approach in which the researcher related the contexts of the data to the data analyzed in order to make replicable and valid inferences from data to its context. The result of the research shows digital literacy skill of the XII grade of SMA Negeri 1 Pecangaan Jepara students is quite good. The reader accepts the aspects of humor through their current contribution on their response inside their peer group.